Aspergillus niger confers health benefits and modulates the gut microbiota of juvenile Pacific white shrimp (Penaeus vannamei) under farming conditions - Zhang, Ming; Liang, Huifen; Lei, Yifan; Zhang, Yiwen; Tan, Zhigang; Chen, Wenzhen; Li, Shengkang; Peng, Xianfeng; Tran, Ngoc Tuan (Frontiers in Marine Science, 2023)
Introduction The fungus Aspergillus niger is found to be predominant in the body of Pacific white shrimp (Penaeus vannamei); however, its role in shrimp’s health has not been explored. This study aimed to evaluate the influences of A. niger on growth, antioxidative activity, immune response, and gut microbiota of juvenile Pacific white shrimps under farming conditions. Methods Shrimps (2.30±1.05 g) were fed diets supplemented with 0 (control), 1.5 (A1.5), or 3.0 g/kg diet of A. niger (A3.0) for one month. At the end of the study, the growth, antioxidant enzyme activity and immune parameters, and gut microbiota in shrimps fed with different experimental diets were analyzed. Results The results showed a significant increase in weight gain, specific growth rate, and length gain of shrimps in A1.5, compared with other groups (P<0.05). With the exception of lysozyme in both A1.5 and A3.0, which were lower than in the control, the activity of superoxide dismutase (SOD), catalase, acid phosphatase, alkaline phosphatase, and phenol oxidase was higher than those in the control. Gene expressions of SOD, anti-lipopolysaccharide factor-ALF1, and ALF2 (in A1.5 and A3.0) and nitric oxide synthase, penaeidin-PEN2 (in A1.5) and PEN3 and PEN4 (in A3.0) were significantly up-regulated compared to the control (P<0.05). The addition of A. niger increased diversity and separated the microbial community in the gut of shrimps. At the phylum level, Firmicutes and Bacteroidota were dominant, and Proteobacteria was less abundant in the A1.5 and A3.0, as compared to the control. At the genus level, the relative abundance of Vibrio, Marivita, and Roseobacter was increased but Ruegeria was decreased in A1.5 and A3.0 when compared to the control. The genera Edwardsiella, Clostridium sensu stricto 1, and Shimia in the A1.5 were higher than in the control. Discussion These findings demonstrated the beneficial effects of A. niger on growth, health, and changes in the gut microbiota in shrimps under farming conditions. The recommended concentration of A. niger in the diet for shrimps is 1.5 g/kg diet.